2006
DOI: 10.1007/s00122-006-0267-5
|View full text |Cite
|
Sign up to set email alerts
|

Conditional QTL mapping of oil content in rapeseed with respect to protein content and traits related to plant development and grain yield

Abstract: Oil content in rapeseed (Brassica napus L.) is generally regarded as a character with high heritability that is negatively correlated with protein content and influenced by plant developmental and yield related traits. To evaluate possible genetic interrelationships between these traits and oil content, QTL for oil content were mapped using data on oil content and on oil content conditioned on the putatively interrelated traits. Phenotypic data were evaluated in a segregating doubled haploid population of 282 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
122
4
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(143 citation statements)
references
References 25 publications
13
122
4
4
Order By: Relevance
“…Furthermore, the mean values of both parental lines and RIL populations showed large difference between environments. Genetic analysis showed that the heritability of oil content in F 5:6 and F 6:7 populations was high (Table 1), which was consistent with previous studies (Zhao et al 2005(Zhao et al , 2006Delourme et al 2006;Wu et al 2006). These results suggested that seed oil content was mainly controlled by genetic factors as compared to environmental factors in these environments.…”
Section: Phenotypic Analysissupporting
confidence: 89%
See 2 more Smart Citations
“…Furthermore, the mean values of both parental lines and RIL populations showed large difference between environments. Genetic analysis showed that the heritability of oil content in F 5:6 and F 6:7 populations was high (Table 1), which was consistent with previous studies (Zhao et al 2005(Zhao et al , 2006Delourme et al 2006;Wu et al 2006). These results suggested that seed oil content was mainly controlled by genetic factors as compared to environmental factors in these environments.…”
Section: Phenotypic Analysissupporting
confidence: 89%
“…Recently, some studies have used parental lines with significant differences in oil content (>10%) (Sun et al 2012;Wang et al 2013), which was useful to detect QTL. These studies showed that QTL for oil content were distributed on 18 of 19 B. napus chromosomes, except chromosome C4 (Ecke et al 1995;Zhao et al 2005Zhao et al , 2006Zhao et al , 2008Zhao et al , 2012Delourme et al 2006;Qiu et al 2006;Sun et al 2012;Wang et al 2013;Jiang et al 2014). The number of QTL detected varied from three (Ecke et al 1995) to 27 (Chen et al 2010) and explained phenotypic variation ranging from 1.2% (Delourme et al 2006) to more than 20% (Chen et al 2010;Sun et al 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genotypespecific and environment-dependent negative correlations between percentage oil and percentage protein in rapeseed seed have been reported (Grami et al, 1977;Gunasekera et al, 2006;Peltonen-Sainio et al, 2011). Closely linked quantitative trait loci for oil and protein contents have been detected in rapeseed (Zhao et al, 2006). These findings demonstrate that a genotypeor environment-dependent tradeoff between the two components is highly relevant; therefore, TAG/protein storage might be manipulated if the underlying mechanisms of control and regulation are understood.…”
Section: In Silico Tag/protein Tradeoff Is Relevant For Crop Improvementmentioning
confidence: 97%
“…This method was first applied to the studies on QTL of developmental behavior in rice (Cheng et al 2013), maize (Osman et al 2013), cotton (Ye et al 2003), soybean (Jiang et al 2010;Han et al 2011), wheat Zhu et al 2011;Jiang et al 2013). Several studies on the analysis of multiple related traits in conditional QTL mapping methods (Zhao et al 2006;Wang et al 2012), defining the genetic relationship among different traits at the QTL level.…”
Section: Introductionmentioning
confidence: 99%